PATIENT’S PERSPECTIVES IN IMPLEMENTATION OF HEALTH PROTOCOL PREVENTING THE TRANSMISSION OF COVID-19 IN THE HEALTH SERVICE ENVIRONMENT BASED ON THE QUALITY OF LIFE (QOL) CONCEPT - YAYAN KURNIAWAN; SUTRI YANI (UNIVED Press, Universitas Dehasen Bengkulu, 2022)
Introduction: Currently, COVID-19 has become a global pandemic. The number of COVID-19 cases in Bengkulu Province in January reached 23.110 cases, while for regional cases, Bengkulu City occupies the highest position, namely 9.015 cases compared to 8 (eight) surrounding districts, which Among them, as many as 158 people died. Transmission of COVID-19 can occur airborne or through air contaminated with the coronavirus, then the virus enters through the nose, eyes, mouth, and other mucous membranes. Discipline in implementing health protocols in the community has reduced transmission. Patients' quality of life undergoing treatment in hospitals during the current COVID-19 pandemic often shows terrible symptoms. Nurses cannot be separated from their responsibilities as severing agents and preventing transmission in the family, community, or health care environment. Aspects of focus in this study's concept of Quality of Life (QOL) are biological health functions, psychological, spiritual, social, and family support. Metode: The design of this research is descriptive phenomenology with a qualitative study method. The total respondents in this study were 15 patients who were taken from 3 treatment rooms (inpatient)—sampling using the purposive sampling method. The criteria for respondents in this study were inpatients, patients with the good general condition, adult patients, and cooperative patients. The data that was explored from the respondents was an overview of the patient's perspective related to efforts to prevent COVID-19 by implementing health protocols in terms of the Quality Of Life (QOL) aspect obtained through in-depth interviews, namely an overview of (1) functions health biologically (physiological), (2) psychological, (3) spiritual, (4) social and (5) family support. Hasil: The results of the analysis obtained from in-depth interviews on the physiological aspect that the application of health protocols is effective in preventing transmission, on the psychological aspect the application of health protocols has an impact on feeling safe in patients, on the spiritual aspect the application of health protocols does not make the patient reduce the value of worship, on the social aspect the patient says that With the application of strict protocols, patients use alternative communication media without having to meet in person so that patients feel protected. Regarding family support, respondents said that the implementation of health protocols could also be adequately realized with full support from the family. Kesimpulan: Implementation related to strict health protocols can be well received and beneficial for the patient's quality of life.